PENGEMBANGAN INTERACTIVE FOLKLORE BOOK BERBANTUAN ARTICULATE STORYLINE UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN SISWA SEKOLAH DASAR - Muhammad Fikri; Yoesrina Novia Vini Syafitri; Hilman Hilmawan; Wawan Darmawan; Ikhlas Rizal Effendi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Reading comprehension remains a persistent challenge in elementary education, particularly when students are required to identify main ideas, infer implicit information, evaluate a text, and retell its content. This study aimed to describe the need, development process, feasibility, and effectiveness of an Interactive Folklore Book assisted by Articulate Storyline for improving fourth-grade students' reading comprehension. The study employed a Research and Development approach using the ADDIE model. The product was an interactive digital storybook entitled “The Legend of Situ Batukarut,” integrating text, illustrations, optional audio, navigation buttons, hotspots, feedback, and activities addressing literal, inferential, critical, and creative comprehension. Needs analysis involved three teachers and 30 students. Product trials consisted of an individual trial with three students, a small-group trial with 40 students, and a large-group trial with 80 students from three elementary schools. Data were collected through interviews, questionnaires, expert validation, tests, and documentation. The data were analyzed descriptively, followed by normality testing, the Wilcoxon signed-rank test, and normalized gain analysis. Teacher and student needs reached 93.33% and 94.17%, respectively. Expert validation produced an average feasibility score of 82.35%, categorized as highly feasible. In the small-group trial, the mean score increased from 52.81 to 74.92 (Z = -5.550; p < .001; N-gain = 0.47). In the large-group trial, it increased from 54.92 to 77.42 (Z = -7.811; p < .001; N-gain = 0.50). The product was therefore highly feasible and effective within the context of this study, although the moderate gain indicates the need for repeated use and further controlled evaluation.